THE STUDENTS’ MATHEMATICAL ABSTRACTION ABILITY THROUGH REALISTIC MATHEMATICS EDUCATION WITH VBA-MICROSOFT EXCEL - Nelly Fitriani; Didi Suryadi; Darhim Darhim (Jurnal Infinity, 2018)
The purpose of this research is to analyze the level of abstraction mathematical ability of the students through learning using Realistic Mathematics Education (RME) with Visual Basic Application (VBA) for Microsoft Excel. This research uses a descriptive qualitative method and the subject of this study is junior high school students of grade 9th in one school in Ngamprah as many as 35 students. One of the instruments in this study is the abstraction test. Results show that as many as 65.71% of students are in the first level of Perceptual Abstraction. As many as 57.14% of students are in the second level of Internalization.  As many as 31.43% of students are in the third level of Interiorization, and as many as 17.14% of students are at the last level, namely Second Level of Interiorization. Overall, the sample in this study can be categorized into four levels of abstraction.